(untitled) (AYUSHDHARA, 2024)
One of the Vatavyadhi induced by vitiated Vata and Kaphanubandha vata is Avabahuka. The symptoms of Avabahuka are similar to those of frozen shoulder, which is brought on by a rotator cuff lesion from the extracapsular cuff, such as partial tears in the supraspinatus tendon. Materials and Procedures: Shodhana Nasya has been recommended for a 49-year-old patient who has complained of discomfort and stiffness in the left shoulder joint and left lateral cervical region, as well as limited movement in these areas. Result: The patient’s symptoms considerably subsided, including decreased neck and left shoulder joint discomfort and stiffness. Discussion: The patient received internal medicine along with Rukshana, Mukhabhyanga, Sarvang Abhyanga, sthanika Patra Pottali Swedana, Sarvanga Swedana, Mashadi Navana Nasya, and Upanaha, which helped to successfully treat the ailment.